Detailed mapping of protected species distribution, an essential tool for renewable energy planning in agroecosystems. (January 2023) - Palacín, Carlos; Farias, Irene; Alonso, Juan Carlos
Abstract: The current development of renewable energy infrastructure (EI) can lead to an irreversible loss of biodiversity, but negative impacts can be minimised through effective planning. As a case study, we identify the essential areas for the conservation of a globally threatened bird, the great bustard ( Otis tarda ). We used 21, 296 observations and the Kernel method to calculate the home-range area of the world's largest population of this species. The home-range area (11, 142 km 2 ) is highly fragmented in small habitat patches (n = 240 areas, mean = 46.42 km 2 ). A large fraction (55.8 %) of this area is outside Special Protection Areas, thus being highly vulnerable to new EI developments. We identified 842.241 km of transport power lines (>50 kV) that intersect with great bustard home-ranges, and therefore may cause collision fatalities of up to 2.46 individuals per km and year. Undergrounding these lines, as well as any other planned lines, is a priority to reduce bird mortality. If EI projects are not well planned, a significant loss of agro-steppe habitat can occur (32.2 % in our control area). We strongly suggest that planning of new EI should take into account the home-range area and flight movements of agro-steppe threatened birds, both inside and outside SPAs. In general, EI projects are assessed on a case-by-case basis, without considering the synergistic effects of all projects that can affect protected species in a region. This work illustrates how large-scale mapping of endangered species is essential for an effective planning of EI. Highlights: The range of the world's largest population of great bustards is highly fragmented. Most of its habitat lies outside Special Protection Areas (SPAs). A significant loss of this habitat may occur due to the development of renewable energy infrastructure (EI). New EI projects must respect this habitat, both inside or outside SPAs. Detailed mapping of protected species is essential for planning of new EI.